SOSIALISASI PROGRAM BOGOR BICARA SEHAT DALAM KONTEKS MENINGKATKAN PEMAHAMAN MASYARAKAT PADA COVID-19 - Naufal Alwan Shiddiq; Feri Ferdinan Alamsyah; Imani Satriani (UNIVERSITAS PAKUAN, 2022)
Bogor Bicara Sehat is an outreach program to the public about Covid-19. Through this program, it will be conveyed to the public that the dangers and impacts of Covid-19 must be realized and anticipated together. This research aims to determine How far do the people of Bogor City understand about Covid-19, to find out the prevention of Covid-19 in the family cluster in Bogor City, and to analyze implementation of Bogor Bicara Sehat Program. This research was conducted in the City of Bogor. This research uses a qualitative approach. The results of this research indicate that implementation of Bogor Bicara Sehat program in increasing understanding of the Covid-19 for the people is effectively. The components of social analysis that are the pillars of this research are: (1) Program, Bicara Project in the Bogor Bicara Sehat Program provides valid and accurate information including education about Covid-19, the impact of the Covid-19 pandemic. (2) Output, aims to provide information to the public about education about the spread of Covid- 19. So that the target of the program is the community, especially the family environment so that the community better understands and understands how to prevent, deal with, and deal with Covid-19 cases. (3) Outcome, Bicara Project in collaboration with the Bogor City Government through the Covid-19 SATGAS to contact every sub-district in Bogor City to be given information and education about Covid-19 and SehatQ prepares and presents doctors to provide material about Covid-19 sourced from the medical.